Generalized model of labour protection system control - Ревук, А. Г.; Гулевец, В. Д. (Proceedings of National Aviation University, 1998)
The problem of improvement of labour conditions can be solved only by means of multilevel measurement-information system of labour protection. The proposed generalized model of labour protection system control by means of multilevel measurement-information system is the basis for formal description of the processes of control with an aim of perfection and optimization of labour control